Analysis of learning anxiety among senior high school students - Taty, Taty (COUNS-EDU: The International Journal of Counseling and Education, 2020)
Learning is the primary task of every student. However, there are many factors responsible for the success or failure such as anxiety, which is the unpleasant feeling of worry, concern, and fear. Therefore this study aims to measure students' anxiety levels in learning and determine efforts to overcome this condition. This is a quantitative descriptive study, with data collected from 192 students using anxiety instruments. The results showed that most students' anxiety levels were in the normal category,  this is because the majority chooses to confide in their close friends.